Field‐Induced Antiferromagnetic Correlations in a Nanopatterned Van der Waals Ferromagnet: A Potential Artificial Spin Ice - Avia Noah; Nofar Fridman; Yishay Zur; Maya Markman; Yotam Katz King; Maya Klang; Ricardo Rama‐Eiroa; Harshvardhan Solanki; Michael L. Reichenberg Ashby; Tamar Levin; Edwin Herrera; Martin E. Huber; et al. (Advanced Science)
Abstract Nano‐patterned magnetic materials have opened new venues for the investigation of strongly correlated phenomena including artificial spin‐ice systems, geometric frustration, and magnetic monopoles, for technologically important applications such as reconfigurable ferromagnetism. With the advent of atomically thin 2D van der Waals (vdW) magnets, a pertinent question is whether such compounds could make their way into this realm where interactions can be tailored so that unconventional states of matter can be assessed. Here, it is shown that square islands of CrGeTe3 vdW ferromagnets distributed in a grid manifest antiferromagnetic correlations, essential to enable frustration resulting in an artificial spin‐ice. By using a combination of SQUID‐on‐tip microscopy, focused ion beam lithography, and atomistic spin dynamic simulations, it is shown that a square array of CGT island as small as 150 × 150 × 60 nm3 have tunable dipole–dipole interactions, which can be precisely controlled by their lateral spacing. There is a crossover between non‐interacting islands and significant inter‐island anticorrelation depending on how they are spatially distributed allowing the creation of complex magnetic patterns not observable at the isolated flakes. These findings suggest that the cross‐talk between the nano‐patterned magnets can be explored in the generation of even more complex spin configurations where exotic interactions may be manipulated in an unprecedented way.